Effects of bronchoscopic alveolar lavage–assisted mechanical ventilation on postoperative pulmonary infection and inflammatory factors in patients undergoing lung cancer surgery - Hui Zhu; Haiyang Lu (Videosurgery and Other Miniinvasive Techniques)
Introduction: Patients undergoing lung cancer (LC) surgery often develop pulmonary infection (PI) due to poor sputum excretion ability leading to accumulation of secretions. Bronchoalveolar lavage (BAL) during fiberoptic bronchoscopy can be used to clear respiratory secretions and serve as a vehicle to locally deliver antibiotics that fight infection.